دراسة اقتصادية لعوائد وتكاليف زراعة الشوندر السكري في منطقة الغاب / محافظة حماة / - جحجاح محسن (Latakia University Journal -Biological Sciences Series, 2019)
يهدف هذا البحث إلى دراسة عوائد وتكاليف زراعة الشوندر السكري في منطقة الغاب (محافظة حماه)، حيث بينت الدراسة أن تكاليف إنتاج الشوندر السكري بلغت 16651ل.س/الدونم، وبلغت قيمة الربح الصافي 7849ل.س/دونم. أما المؤشرات الاقتصادية فقد بلغت قيمة أو نسبة كل منها وفقا للآتي: الهامش الإجمالي للربح 14028ل.س/الدونم، والربح الاقتصادي 9228ل.س/الدونم، ومعامل رأس المال المتغير2.34، أما الكفاءة الإجمالية الاقتصادية فبلغت 1.47%، وتم حساب معامل الربحية الذي بلغ 62%، أما زمن استعادة راس المال بلغ 2.1سنة، وبلغ معامل الريعية للاستثمارات 128.48%. This research aims aims to study the proceeds and cost of growing the sugar beet in Al-Ghab region(Hama). The study showed the cost of production for the sugar beet reached16650 SP and the clear profits reached 7849 SP while the economic indexes has recorded the gross mergin of profits 14028 SP ,economic profits 9228 SP and the factories of cheangable2.34 while the economic gross qualification reached 1.47%, the profit factories has accounted which reached 62% while the time of retrie variable of capitay reached 2.1 year, the rentabilite factories of in vestment 128.48%.